When Was Latin America Modern?
VI, 217 p.
Keywords: Stemming from an interdisciplinary convention in 2005 at the Institute for the Studies of the Americas in London, this collection has a strong thematic integrity, but also illustrates the dramatic variety of approaches to the question of modernity. This volume fills the gaps in prior literature on Latin America's experience of modernity.